Incorporating VR, AR and related technologies in tourism industry: State of the art - Loureiro, S. M. C. (2022)
The current chapter intends to expose the importance of tourism in the world economy, (ii) give an overview of what academic and practitioners are doing regarding the use of engagement-facilitating technologies in tourism, and (iii) suggest avenues for further research. Thus, first the authors give insights about the evolution and important of tourism. After that, the chapter presents an overview of the state of the art on the use of engagement-facilitating technologies (mainly virtual and augmented reality) in research. The examples of applications of engagement-facilitating technologies come next. In the end, the authors suggest future research directions and present the conclusions.